Wellbeing in Future Urban Landscapes in the City of Manila - Villlanueva, Cecilia May S.; Mical, Thomas E. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment; Issue Number 9, 2023)
Wellbeing in future urban landscapes are distributed and connected green spaces intertwined with architecture and urbanism as networks and lattices of urban biodiversity. Wellbeing and spirituality in the Filipino culture relates to the calm and peace that can be found in natural surroundings and access to basic needs. This study aims to forge partnerships with major stakeholders, identify best practices and consult with experts on possible wellbeing interventions in Manila’s future landscape. Furthermore, this study intends to utilize existing community resources to design grassroots innovations for wellbeing in the current and future tense. A series of focused group discussions and community meetings links collaborative efforts in engaging the different stakeholders in the study area. Results show that a linked green infrastructure is best achieved from a bottom-up initiative reinforced by technical experts in showcasing grassroots best practices that sustain programs on wellbeing in future landscapes. Devolving leadership at the barangay level strengthens cooperation of public, private and other agencies. Information and communication technology is vital in maintaining linkages during this time of multiple disruptions. An openness to multi-sectoral collaboration and extending technical expertise to communities are deeply rooted in the Filipinos “bayanihan” spirit.